Answer:
An equation in standard form for the line is:
![\frac{5}{2}x-y=-4](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7Dx-y%3D-4)
Step-by-step explanation:
Given the points
The slope between two points
![\mathrm{Slope\:between\:two\:points}:\quad \mathrm{Slope}=\frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=%5Cmathrm%7BSlope%5C%3Abetween%5C%3Atwo%5C%3Apoints%7D%3A%5Cquad%20%5Cmathrm%7BSlope%7D%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
![\left(x_1,\:y_1\right)=\left(-2,\:-1\right),\:\left(x_2,\:y_2\right)=\left(0,\:4\right)](https://tex.z-dn.net/?f=%5Cleft%28x_1%2C%5C%3Ay_1%5Cright%29%3D%5Cleft%28-2%2C%5C%3A-1%5Cright%29%2C%5C%3A%5Cleft%28x_2%2C%5C%3Ay_2%5Cright%29%3D%5Cleft%280%2C%5C%3A4%5Cright%29)
![m=\frac{4-\left(-1\right)}{0-\left(-2\right)}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B4-%5Cleft%28-1%5Cright%29%7D%7B0-%5Cleft%28-2%5Cright%29%7D)
![m=\frac{5}{2}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B5%7D%7B2%7D)
Writing the equation in point-slope form
As the point-slope form of the line equation is defined by
![y-y_1=m\left(x-x_1\right)](https://tex.z-dn.net/?f=y-y_1%3Dm%5Cleft%28x-x_1%5Cright%29)
Putting the point (-2, -1) and the slope m=1 in the line equation
![y-\left(-1\right)=\frac{5}{2}\left(x-\left(-2\right)\right)](https://tex.z-dn.net/?f=y-%5Cleft%28-1%5Cright%29%3D%5Cfrac%7B5%7D%7B2%7D%5Cleft%28x-%5Cleft%28-2%5Cright%29%5Cright%29)
![y+1=\frac{5}{2}\left(x+2\right)](https://tex.z-dn.net/?f=y%2B1%3D%5Cfrac%7B5%7D%7B2%7D%5Cleft%28x%2B2%5Cright%29)
![y=\frac{5}{2}x+4](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5%7D%7B2%7Dx%2B4)
Writing the equation in the standard form form
As we know that the equation in the standard form is
![Ax+By=C](https://tex.z-dn.net/?f=Ax%2BBy%3DC)
where x and y are variables and A, B and C are constants
so
![y=\frac{5}{2}x+4](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B5%7D%7B2%7Dx%2B4)
![\frac{5}{2}x-y=-4](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7Dx-y%3D-4)
Therefore, an equation in standard form for the line is:
![\frac{5}{2}x-y=-4](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B2%7Dx-y%3D-4)
Answer:
What happened frnd?
plz answer me!
have a great and pleasant day ahead
$10.71
Explanation
Step 1
you can easily solve this by using a rule of three.
Let
x represents the money Eileen will pay if her bag weighs 63 pounds
the proportion is the same
then
![\frac{7.14}{42}=\frac{x}{63}](https://tex.z-dn.net/?f=%5Cfrac%7B7.14%7D%7B42%7D%3D%5Cfrac%7Bx%7D%7B63%7D)
Step 2
solve for x
![\begin{gathered} \frac{7.14}{42}=\frac{x}{63} \\ 63\cdot7.14=42x \\ x=\frac{63\cdot7.14}{42} \\ x=\frac{449.82}{42} \\ x=10.71 \\ \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20%5Cfrac%7B7.14%7D%7B42%7D%3D%5Cfrac%7Bx%7D%7B63%7D%20%5C%5C%2063%5Ccdot7.14%3D42x%20%5C%5C%20x%3D%5Cfrac%7B63%5Ccdot7.14%7D%7B42%7D%20%5C%5C%20x%3D%5Cfrac%7B449.82%7D%7B42%7D%20%5C%5C%20x%3D10.71%20%5C%5C%20%20%5Cend%7Bgathered%7D)
I hope this helps you